18F-FDG PET/CT and extragastric MALT lymphoma: role of Ki-67 score and plasmacytic differentiation. Issue 10 (3rd October 2017) - Albano, Domenico; Bosio, Giovanni; Giubbini, Raffaele; Bertagna, Francesco
Abstract: The detection rate of fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in extragastric mucosa associated lymphoid tissue (MALT) lymphoma is under debate and the reason is not clear. Our aim was to investigate the metabolic behavior of extragastric MALT lymphoma and whether the histological features (Ki-67 index and plasmacytic differentiation, PD) might explain it. PET/CT images were analyzed visually and semi-quantitatively and compared with Ki-67 index and PD. Seventy-two patients were included. Twelve of 18 patients with PD showed intense 18F-FDG uptake; on the contrary, 42 of 54 patients without PD had positive 18F-FDG PET/CT. Twenty-six of 27 patients with Ki-67 > 15% had 18F-FDG-avid lesions; 28 of 45 patients with Ki-67 ≤ 15% had positive 18F-FDG PET/CT. 18F-FDG avidity was significantly associated with Ki-67 index ( p  < .001) and not correlated with PD ( p  = .352). Maximum standardized uptake value (SUVmax), lesion-to-liver SUVmax ratio and lesion-to-blood pool SUVmax ratio were not correlated with Ki-67 index or PD. 18F-FDG avidity was noted in 75% and is correlated only with Ki-67.